Relationship between improved airflow limitation and changes in airway calibre induced by inhaled anticholinergic agents in COPD. Issue 4 (15th December 2008) - Hasegawa, M; Makita, H; Nasuhara, Y; Odajima, N; Nagai, K; Ito, Y; Betsuyaku, T; Nishimura, M
Abstract : Background: Although airflow limitation improved by inhaled anticholinergic drugs varies among individuals with chronic obstructive pulmonary disease (COPD), the relationship between actual bronchodilation and improved pulmonary function and where in the lung such bronchodilation occurs remains unknown. A study was undertaken to determine the relationship between improved pulmonary function and changes in airway calibre at various sites in the airways in response to inhaled anticholinergic agents in patients with COPD using three-dimensional computed tomography (CT). Methods: CT scans were performed at deep inspiration and detailed pulmonary function tests before and 1 week after daily inhalations of tiotropium bromide in 15 patients with clinically stable COPD. The airway luminal area was examined at the third (segmental) to the sixth generations of eight bronchi in the right lung. Results: Bronchodilation was demonstrated by an overall average increase of 39% in the inner luminal area, and the mean (SE) forced expiratory volume in 1 s (FEV1 ) increased from 1.23 (0.11) l to 1.47 (0.13) l. The magnitude of bronchodilation was closely correlated with improved pulmonary function, particularly with that of FEV1 (r = 0.843, p<0.001). Such correlations were significant at the fourth to the sixth generation but not at the third generation of bronchi, and the slope of the regression lines became steeper from the third to the sixth generation. Conclusions: Inhaled anticholinergic agents induce overall bronchodilation which is in proportion to improvements in FEV1 in patients with COPD. Bronchodilation at the distal rather than the proximal airways is the determinant of functional improvement.